On a class of filters in the Watson Fourier wavelet setting - Loualid, El. M.; Laadissi, El. M.; Ennawaoui, C. (Methods of Functional Analysis and Topology, 2021)
In this paper, using the theory of harmonic analysis related to the Watson-Fourier transform, we study a linear time invariant filter. Also, we show that this linear time invariant filter can be expressed in the form of Watson Fourier wavelet transform. Finally, the Fredholm integral equation is defined and we give a solution of this integral equation. Next, an application of the linear time invariant filter is given in the theory of the aforesaid integral equation. У даній роботі, використовуючи пов’язаний з перетворення Уотсона-Фур’є гармонічний аналіз, вивчено лінійний інваріантний за часом фільтр. Показано, що цей лінійний інваріантний за часом фільтр може бути представлений у вигляді вейвлет-перетворення Уотсона Фур’є. Також визначено інтегральне рівняння Фредгольма і наведено розв’язок цього інтегрального рівняння. Надано застосування лінійного інваріантного за часом фільтра до теорії вищезгаданого інтегрального рівняння.